The preliminary validity and reliability of the Assessment of Barriers to Learning in Education – Autism. (September 2021) - Howell, Melanie; Bailey, Tom; Bradshaw, Jill; Langdon, Peter E.
Highlights: A new autism-specific, special needs teacher assessment was tested. Results showed excellent test-retest reliability and internal consistency. The assessment strongly correlated with the Teacher Autism Progress Scale. Teacher feedback was extremely positive. Results suggest the ABLE-Autism is a useful and effective assessment. Abstract: Background: Few robust autism-specific outcome assessments have been developed specifically for use by teachers in special schools. The Assessment of Barriers to Learning in Education – Autism (ABLE-Autism) is a newly developed teacher assessment to identify and show progress in barriers to learning for pupils on the autism spectrum with coexisting intellectual disabilities. Aims: This study aimed to conduct a preliminary validity and reliability evaluation of the ABLE-Autism. Methods and procedures: Forty-eight autistic pupils attending special schools were assessed using the ABLE-Autism. Multi-level modelling was used to evaluate test-retest reliability, internal consistency and convergent validity with the Teacher Autism Progress Scale. Outcomes and results: Results showed excellent test-retest reliability and internal consistency. A large effect size suggested that the ABLE-Autism is strongly correlated with the Teacher Autism Progress Scale. Teacher feedback was positive and suggested that the ABLE-Autism is easily understood by teachers, relevant to autistic pupils in special schools, and adequately covers the skills and behaviours that teachers believe are important to assess for these pupils. Conclusions and implications: Although further validation is recommended, the preliminary evaluation of the ABLE-Autism suggests that it is a useful and has the potential to be an effective outcome assessment for autistic pupils in special schools.